2017
DOI: 10.1055/s-0037-1606352
|View full text |Cite
|
Sign up to set email alerts
|

The 2014–2015 National Impact of the 2014 American Academy of Pediatrics Guidance for Respiratory Syncytial Virus Immunoprophylaxis on Preterm Infants Born in the United States

Abstract: Objective  This article aims to compare respiratory syncytial virus (RSV) immunoprophylaxis (IP) use and RSV hospitalization rates (RSVH) in preterm and full-term infants without chronic lung disease of prematurity or congenital heart disease before and after the recommendation against RSV IP use in preterm infants born at 29 to 34 weeks' gestational age (wGA). Study Design  Infants in commercial and Medicaid claims databases were followed from birth through first year to assess RSV IP and RSVH, as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 28 publications
4
49
0
Order By: Relevance
“…Our results are in line with those of previous analyses that found substantially decreased outpatient RSV IP use and increased RSVH risk among preterm infants after the AAP policy change. 9,[20][21][22] In single-center studies by Rajah et al and Blake et al, RSVH rates for preterm infants were significantly greater in post-versus pre-policy change RSV seasons. 9,21 Similarly, administrative claims analyses utilizing a patient population comparable to ours from the Truven Health MarketScan database showed that RSVH risk among preterm infants increased significantly in the 2014 to 2015 season compared with the 2013 to 2014 season, 20 and in the 2014 to 2016 seasons compared with the 2012 to 2014 seasons.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results are in line with those of previous analyses that found substantially decreased outpatient RSV IP use and increased RSVH risk among preterm infants after the AAP policy change. 9,[20][21][22] In single-center studies by Rajah et al and Blake et al, RSVH rates for preterm infants were significantly greater in post-versus pre-policy change RSV seasons. 9,21 Similarly, administrative claims analyses utilizing a patient population comparable to ours from the Truven Health MarketScan database showed that RSVH risk among preterm infants increased significantly in the 2014 to 2015 season compared with the 2013 to 2014 season, 20 and in the 2014 to 2016 seasons compared with the 2012 to 2014 seasons.…”
Section: Discussionmentioning
confidence: 94%
“…Several U.S. studies have demonstrated an increase in RSVH risk among infants 29 to 34 wGA and < 6 months CA under the more restrictive recommendations. 9,[20][21][22] These findings would benefit from validation in other large datasets. In addition, the effect of the policy change on RSVH severity and costs has not been evaluated.…”
mentioning
confidence: 81%
“…Additionally, three recent studies demonstrate the rate of RSVH in infants 29 to 34 wGA compared with term infants has increased since the release of the 2014 COID guidance. 27,29,30 Another limitation of this study is that although hospital charges are reported, actual reimbursement amounts may differ. Hospital charges reported here do not include physician fees and also do not account for reimbursements that are commonly negotiated between hospitals and insurance carriers.…”
Section: Discussionmentioning
confidence: 99%
“…11 Two recent large retrospective studies using commercial and Medicaid insurance databases compared RSV hospitalization rates in premature infants before and after the 2014 AAP guidance change, and included healthy full-term infants as a reference. 12,13 Authors showed again that RSV-associated hospitalizations in infants born at 29 to 34 wGA and < 3 months of age increased up to 2.7-fold after the guidance change. They also showed that compared with fullterm infants, premature infants had up to seven times higher risk for RSV-associated hospitalizations.…”
Section: Current Trends In Rsv-associated Morbidity In Premature Infantsmentioning
confidence: 97%